P-N ўтишли диодларнинг Ферми Квази сатҳи ва волть – ампер характеристикасига микотўлқин таъсири (SCIENCE and SOCIETY, 2022)
The quasi-levels of electrons and holes are studied in semiconductors in a strong microwave field. It is shown that the- se changes in the Fermi quasi-level strongly affect the current-voltage characteristic of a semiconductor diode with a p-n junction.